2021
DOI: 10.26434/chemrxiv.14317649.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical Spectroscopy of Crystal Nucleation One Nucleus at a Time

Abstract: <p>Crystallization is an important process in a wide range of disciplines from fundamental science to industrial application. Despite the importance of controlling the crystallization and its morphology (<i>e.g.</i> polymorphism), the lack of microscopic description of crystal nucleation often limits the rational approach to its engineering and control. The biggest challenge to experimentally track the nucleus formation is the stochastic and heterogeneous nature of the nucleation occurring at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Another photophysical approach is "optical trapping-induced crystallization (OTIC)" where condensation of solute molecules (and/or clusters) at laser focus via optical trapping triggers nucleation. 11,12 Noteworthy, the studies of NPLIN and OTIC also demonstrated the polarization-dependent polymorphism, 2−4 of which mechanism has been discussed based on interactions between polarizability tensors of solute molecules (and/or clusters) and photoelectric fields and/or difference in bubble formation behavior with polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Another photophysical approach is "optical trapping-induced crystallization (OTIC)" where condensation of solute molecules (and/or clusters) at laser focus via optical trapping triggers nucleation. 11,12 Noteworthy, the studies of NPLIN and OTIC also demonstrated the polarization-dependent polymorphism, 2−4 of which mechanism has been discussed based on interactions between polarizability tensors of solute molecules (and/or clusters) and photoelectric fields and/or difference in bubble formation behavior with polarization.…”
Section: Introductionmentioning
confidence: 99%